Resistance Patterns of Escherichia coli and Klebsiella pneumoniae Bacteria Against Amikacin, Ceftazidime, Meropenem, Nitrofurantoin Antibiotics in Elderly Patients with UTI in RSUD Dr. Soetomo - Herdiyanti Herdiyanti; Lindawati Alimsardjono; Danti Nur Indiastuti (Faculty of Medicine Universitas Airlangga, 2019)
Introduction: Urinary tract infection (UTI) is an infection that involves the urinary tract, including the urethra, bladder, ureter, and kidneys. UTI is caused by microorganisms that breed in the urinary tract which are supposed to be free of microorganisms. Two bacterias that cause UTI in general are Escherichia coli and Klebsiella pneumoniae. UTI can occur at any age but generally occurs in the elderly. UTI caused by gram-negative bacteria can be killed with several examples of antibiotics namely amikacin, ceftazidime, meropenem and nitrofurantoin. These antibiotics found resistance to the bacteria that cause the UTI. This research is to determine the resistance patterns of Escherichia coli and Klebsiella pneumoniae bacteria against amikacin, ceftazidime, meropenem, nitrofurantoin antibiotics in elderly patients with UTI in Dr. Soetomo Surabaya January-June 2017 period.Methods: A descriptive retrospective study in accordance with the logbook data of Clinical Microbiology Installation at Dr. RSUD. Soetomo Surabaya. Data from this study were taken from all populations that met the inclusion criteria. The results are presented by tables. Results: There are 163 elderly patient data which diagnosed with urinary tract infection. Escherichia coli resistance pattern against ceftazidime (75.6%), nitrofurantoin (12.6%) and meropenem (2.4%). Meanwhile, Klebsiella pneumoniae against ceftazidime (72.2%), nitrofurantoin (55.6%), meropenem (11.1%) and amikacin (2.8%). Conclusion: There were resistance number of Escherichia coli and Klebsiella pneumoniae bacteria against antibiotics amikacin, ceftazidime, meropenem, nitrofurantoin in elderly patients with UTI.